Globalisation of Islamic Financial Services and World City Networks - Hasan, Abul (Journal of Islamic Finance, 2015)
Islamic Financial Services (IFSs) sector is rapidly developing in the Middle East cities as well as growing in the South East Asian cities like Kuala Lumpur and Jakarta. Growth rate of this sector is notably significantly in the mainstream International Financial Centres (IFCs) such as London and New York. Currently these cities are said to be the ‘command and control’ centres of the global economy because they harbour producer's services firms which manage increasingly complex production networks. This paper draws an analysis of rapidly expanding IFSs sector through a study of how cities are being connected through the intra-firm networks which provide Shari‘ah-compliant financial services. It is argued that a focus on the globalisation of Islamic financial services (IFS) sector may provide an alternative to hegemonic imaginations of world city-formation through its focuses on globalising economic process. The relevance of such analysis is discussed against the conceptual backdrop of the world city network literature. Based on information on the location  strategies of 27 leading Islamic financial services (IFS) firms in 47 cities across the world, this study employed the methodology on ‘globalisation and world city network’ (GaWC). The results show that globalisation within the Muslim world follows a unique urban trajectory, thereby creating a network of powerful cities. The results also show that Middle East is at the apex of the IFSs sector and Manama is identified the hub of the IFS sector which other major cities such as Amman, Dubai, Doha, Jakarta, Jeddah, Karachi, Kuala Lumpur, Kuwait, Riyadh and Istanbul etc. are also primary nodes in the city network. Outside the Muslim world, London is increasingly profiling itself as a global Islamic financial service (IFS) hub.